Exploring the Achievement Gap Between White And Minority Students in Texas - Linton, Thomas H.; Kester, Donald (Education Policy Analysis Archives, 2003)
The Texas Assessment of Academic Skills (TAAS) has been used to document and track an achievement gap between white and minority students in Texas. Some educators have credited the TAAS with fueling a drive to close the achievement gap while others suggest that TAAS scores may be misleading because of factors such as score inflation and a possible ceiling effect. The purpose of this study was to analyze the gap in mathematics achievement for eighth grade students. The study compared TAAS and National Assessment of Educational Progress (NAEP) test results to determine if the achievement gap between white, Hispanic, and African-American Students had narrowed between 1996 and 2000. Results indicate that TAAS mean scores increased significantly for all three ethnic groups between 1996 and 2000. Comparison of the TAAS test score frequency distributions for each ethnic group indicated that white students' scores shifted from the middle to the upper portion of the test score range while minority students' scores shifted from the lower to the middle and higher score range. Both white and minority students' TAAS test score distributions were significantly more negatively skewed in 2000 than in 1996. Comparisons between white and minority students' TAAS scores showed that white students had significantly higher scores than either Hispanic or African-American students in both 1996 and 2000. Comparison of mean score differences in 1996 and 2000 indicated that the achievement gap between white and minority students had narrowed. NAEP scores increased significantly from 1996 to 2000 for Hispanic students, but not for white or African-American students. However, test score distribution patterns showed small positive changes for all three ethnic groups. Comparisons between ethnic groups indicated that there were significant differences between white and minority students' scores in both 1996 and 2000. Comparison of mean score differences in 1996 and 2000 indicated that the achievement gap between Hispanic white students had narrowed slightly but that there was no change in the achievement gap between white and African-American students. Analysis of the TAAS test score distribution patterns indicated the likelihood that a ceiling effect had impacted students' scores. The evidence for a ceiling effect was strongest for white students. In 2000, 60.4% of white students had a TAAS score that fell in the top 10% of the score range. In contrast, there was no evidence of a ceiling effect for the NAEP. Mean score gains on the TAAS are only partially substantiated by the NAEP data. Furthermore, there is a very strong possibility that a ceiling effect artificially restricted the 2000 TAAS scores for white students and created the illusion that the achievement gap between minority and white students had been narrowed.